The Model for Maintaining Families with Noble Character During the Pandemic in Kampung KB Villages - Kustati, Martin; Kosim, Muhammad; Sermal, Sermal; Fajri, Suryadi; Febriani, Suci Ramadhanti (SCAD Independent, 2024)
This research is motivated by the lack of family resilience during the Covid-19 pandemic, especially from the perspective of Islamic education. So, research and development are needed to increase the resilience of character families. This research aimed to identify how the profile of family resilience with the Character of an Islamic education perspective during the Covid-19 pandemic in the family planning village and how the characteristic of family resilience with the Character of an Islamic education perspective during the Covid-19 pandemic in a family planning village that is valid, practical, and effective. The method used was research and development with qualitative and quantitative data approaches. The results were obtained through research on the Character Family Resilience Profile and Character Family Resilience Module. The family resilience profile based on the Islamic Education Perspective was characterized by five characteristics: Nationalism, independence, Mutual Cooperation, and Integrity as well as a character family resilience module during a pandemic in the KB village, which had been developed through a self-evaluation process, validation with five validators, one-on-one evaluation process, small group evaluation and extensive group evaluation resulting in a very valid, practical and effective module.